2018
DOI: 10.5114/wiitm.2018.72683
|View full text |Cite
|
Sign up to set email alerts
|

Video-assisted-thoracoscopic surgery in left-to-right Nuss procedure for pectus excavatum for prevention of serious complications - technical aspects based on 1006 patients.

Abstract: IntroductionAdditional use of the video-assisted thoracoscopic surgery (VATS) technique in the Nuss procedure has been globally accepted for the improvement of safety of surgical treatment as well as for decreased frequency of serious intraoperative and postoperative complications.AimTo evaluate VATS in surgical treatment of patients with pectus excavatum by the left-to-right Nuss procedure for prevention of serious intra- and postoperative complications.Material and methodsFrom 2002 to 2016, 1006 patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
4
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 25 publications
5
4
0
2
Order By: Relevance
“…Our nding was consistent with previous reports when both revealed that elderly patients need to put more metal bars compared to younger patients [21], [22]. The number of patients receiving 2 metal bars was lower in our study than in previous studies [21], [22]. For instance, in an early report by Pilegaard HK, 121 patients were inserted with 1 metal bar (66.8%), 57 cases were inserted with 2 metal bars (32%), and 2 cases were inserted with 3 metal bars (1.2%) [22].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our nding was consistent with previous reports when both revealed that elderly patients need to put more metal bars compared to younger patients [21], [22]. The number of patients receiving 2 metal bars was lower in our study than in previous studies [21], [22]. For instance, in an early report by Pilegaard HK, 121 patients were inserted with 1 metal bar (66.8%), 57 cases were inserted with 2 metal bars (32%), and 2 cases were inserted with 3 metal bars (1.2%) [22].…”
Section: Discussionsupporting
confidence: 93%
“…The 2-bar insertion was indicated for most elderly patients with severe PE and wide concave area; no case was placed with 3 metal bars. Our nding was consistent with previous reports when both revealed that elderly patients need to put more metal bars compared to younger patients [21], [22]. The number of patients receiving 2 metal bars was lower in our study than in previous studies [21], [22].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…No case in our institution had three metal bars placed yet. Our finding was consistent with previous reports when both revealed that the number of implanted steel bars was greater with age (18)(19)(20). Compared to previous studies (19,20), the number of patients receiving two metal bars was lower in our study.…”
Section: Discussionsupporting
confidence: 92%
“…Our finding was consistent with previous reports when both revealed that the number of implanted steel bars was greater with age (18)(19)(20). Compared to previous studies (19,20), the number of patients receiving two metal bars was lower in our study. The patient's chest wall becomes more solid after puberty and harder to bend; hence, introducing more than one bar is done to prevent postoperative pain and pressure on the chest wall by preventing displacement of the bar.…”
Section: Discussionsupporting
confidence: 92%